Polyelectrolytes inhibition effect on crystallization of gypsum - Dogan, Ö; Akyol, E; Öner, M (WILEY-V C H VERLAG GMBH, 2004)
The spontaneous precipitation of calcium sulfate dihydrate (gypsum) at 30 degreesC was investigated in the presence of polyelectrolytes. The degree of inhibition is measured as the reduction in initial crystallization rate, determined by conductivity of the crystallizing solution. The inhibition increases with acid content of the copolymer. Changing the butyl ester to a hydrophilic ethylene oxide resulted in higher inhibition efficiency. The inhibition efficiency is believed to arise from the closer chain packing on the crystal surface.
Keywords: crystal growth inhibition; gypsum precipitation; habit modification; polyelectrolytes; CALCIUM-SULFATE; COPOLYMERS; SURFACES; DESIGN; Crystallography